HUBUNGAN ANTARA HEALTH LOCUS OF CONTROL DENGAN KEPATUHAN MENJALANI TERAPI HEMODIALISIS PADA PASIEN GAGAL GINJAL TERMINAL - Nyoman Kartika Suryani; Gusti Ayu Ary Antari; Ni Komang Ari Sawitri (Coping: Community of Publishing in Nursing, 2021)
Kidney failure is a chronic renal disease that has the characteristics of decreasing the glomerular filtration rate to <15 ml/min/1.73m2 and is irreversible. Patients are required to have hemodialysis as their life sustaining treatment. Health Locus of Control (HLC) is one of the factors that can affect the patient’s adherence in the hemodialysis therapy. This study was purposed to determine the relationship between health locus of control and adherence of hemodialysis therapy on patients with kidney failure. A correlative descriptive study with cross-sectional approach was implemented as the design of this study. Respondents of 100 people were obtained through a purposive sampling technique. Spearman rank test was applied to get the data analysis. The results showed that there were a positive weak relationship between internal HLC and adherence (r=0.236; p-value=0.018; ?=0.05), a positive moderate relationship between powerful others HLC and adherence (r=0.416; p-value=0.001; ?=0.05) and there was no relationship between chance of HLC and adherence (p-value=0.564; ?=0.05). It is expected that this research can inform nurses in improving patients’ adherence in hemodialysis therapy